Research Guide to People's Daily Editorials, 1949-1975 - Oksenberg, Michel; Henderson, Gail (University of Michigan Press, 2020)
An indispensable aid to researching a crucial series of policy statements, the present guide provides access to the only continuous source from China which illuminates high-level policy. Includes an extensive subject index.